Synthesis and conformational study of 1,1′-ethano-9-9′-bifluorenyl. Anti and gauche conformers of a 9,9′-bifluorenyl derivative and chair and twist conformers of a dibenzo-1,5-cyclooctadiene derivative - Lai, Y.-H. (2014)
Tetrahedron